Available drugs during of military state: social-economic strategies of functioning reimbursumen’t system - Peklina, G.; Kovalevskaya, L.; Antipov, N.; Peklina, S.; Smirnova, A. (Journal of Education, Health and Sport, 2023)
The Russian aggresion against Ukraine became a new reality in the XXI century and definitely shook the whole World. New realities are forcing all spheres of science and practice to work harder and develop, that is why philosophers of law are tended to call war “the driving force of progress”. Our modern life in the condition of war proves, that the technical and scientific progress as it is, is created and developed on thousands and millions of destroyed human lives. But, in order to make a warring society to move successfully forward, save as many innocent lives as possible and meet basic needs of a particularly vulnerable polutation, it is not only army, which is supposed to work for 100%, but also “home front workers” has to try harder. The current war has dimished an understanding of difference between quintiles of population, especially, if we are taking into account differences between beneficiaries of the Affordable Medicines Program (AM). At the beginning of the War, all beneficiaries of the AM, despite of level of their well-being had to suffer equally because of the short-term period of medicines’ shortage due to destroyed infrastructure of cities and regions. They were afraid that those highly necessary medicines would not return to the pharmacies neither in the sphere of the AM, nor even for normal sale. Because of the aforementioned force-majeure, most of people were not even assured that their basic needs will be met, especially were worried those ones, who have been active users of the AM for a long period of time. However, despite of the aforementioned destruction of the insfrastrucutre, the commons fears and dangers of war, the AM has not stopped working. On the contrary, it has become even more successful and progressive. The need to react quickly to the circumstances that took place, forced to achieve long-term plans of the AM creators in a very short time. Thus, the pilot program has finally fit into the general outline of the life support and health care system of Ukraine and became perhaps the most progressive in the whole Europe. But, nevertheless, the progress is definitely not standing still, the situation remains critical, the humanitarian catastrophe is becoming more and more real today, and, thus, the AM opens new promising ways of development for the coming month and years. In fact, our study was devoted to the analysis of the changes that took place since February 24, 2022, as well as promising directions for the development of AM, which are mostly dictated by the newly created humaniatrian crises in the current article.